Pengaruh COVID-19, Faktor Fundamental Ekonomi, dan Indeks Saham Acuan Amerika Serikat terhadap Indeks Harga Saham Gabungan (IHSG) selama Pandemi COVID-19 - Prayogo, Selvina Intan; Sakti, Imanuel Madea (Benefit: Jurnal Manajemen dan Bisnis, 2024)
This study aims to empirically examine the effect of positive and death cases from COVID-19, the exchange rate, the Dow Jones Index, and the NASDAQ Index on the Jakarta Composite Index (JCI). This study used time series data which divided into three periods, namely the initial period of the pandemic (2 March 2020 - 31 August 2020), the new normal period (1 September 2020 - 1 March 2021), and the vaccination period (2 March 2021 - 31 August 2021). This study used quantitative methods with multiple regression analysis techniques. This study added a robustness check by using positive and death cases of COVID-19 as moderating variables. The results showed that the IDR/USD exchange rate and the Dow Jones index, respectively, had a negative and positive effect on the JCI. Meanwhile, positive and death cases of COVID-19 and the NASDAQ index had no effect on the JCI. However, the results of the robustness test suggested that the COVID-19 cases indirectly strengthened and weakened other variables on the JCI.